Pengaruh Suku Bunga Acuan dan Dana Pihak Ketiga (DPK) Perbankan Terhadap Dana Kelolaan (AUM) Reksa Dana Bersifat Terbuka (Open End Fund) Periode 2020 -2024 - Sejati, Shandi Setya; Sibarani, Mentiana (Indo-MathEdu Intellectuals Journal, 2025)
This study investigates how monetary policy dynamics icy and the growth of banking third party funds (DPK) which are thought to affect the assets under management (AUM) of open-ended mutual funds for the 2020-2024 period. The theoretical foundation discusses three main variabels: AUM of open-ended mutual funds as the dependent variabel, and benchmark interest rates and bank deposits as independent variabels. This research uses a quantitative approach with multiple linear regression methods, utilizing monthly secondary data from Bloomberg, Bank Indonesia, and the Financial Services Authority (OJK). Classical assumption tests include normality, multicollinearity, and heteroscedasticity tests, followed by the F test, t test, and coefficient of determination (R²) test. The results of the analysis show that the benchmark interest rate has no significant effect on the AUM of open-ended mutual funds partially, while the Third Party Fund of banks has a significant negative effect. Simultaneously, both have an effect on the dependent variabel, with bank Third Party Funds showing greater dominance than the benchmark interest rate in influencing changes in AUM. This study concludes that the strategies of investment managers and regulators need to be directed at strengthening literacy, product innovation, and the synergy of banking-capital market sector policies so that the mutual fund industry can develop more optimally in Indonesia.